Promoting Inferential Reading Skills through Contextual Clues in EFL Instruction - Awaludin Rizal; Abdulhalim Daud; Silvani Umar Ali; Fachria Yamin Marasabessy; Hamida Ahmad Jasin; Ridayani Ridayani; Nursalim Nursalim (PT. Global Research Collaboration, 2026)
This study examines the effect of teaching contextual clues on enhancing inferential reading skills among English as a Foreign Language (EFL) learners. A quasi-experimental design was employed, involving two intact classes of intermediate EFL students who were divided into experimental and control groups. The experimental group received specialised instruction on recognising and using contextual clues to draw inferences while reading, whereas the control group continued with traditional reading instruction without a focus on inferential strategies. Both groups participated in pre- and post-tests to measure their inferential reading abilities. The results showed a significant improvement for the experimental group, whose average score increased from 65.97 on the pre-test to 86.72 on the post-test. In contrast, the control group’s mean score rose only slightly, from 68.44 to 73.59, with minimal change in standard deviation, indicating limited progress using standard teaching methods. These outcomes emphasize the importance of integrating contextual clue instruction into EFL reading curricula to develop stronger inference-making and overall reading comprehension skills. The study highlights the significant benefits that such instructional strategies offer EFL learners and suggests that curriculum designers and educators should consider incorporating these approaches to better support students’ language development and academic success.